A reinforced porous membrane and preparation method thereof

The silane coupling agent coating formed by crosslinking on the surface of the porous membrane solves the problem of insufficient mechanical properties of the porous membrane, significantly improves its mechanical properties, and maintains the fluid flux and dissolution and precipitation performance.

CN118454476BActive Publication Date: 2025-04-15MEMBRANE SOLUTIONS ADVANCED MATERIAL TECH (CHONGQING) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410554579.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2025-04-15
Estimated Expiration
2044-05-07

AI Technical Summary

Technical Problem

The existing porous membrane has low mechanical properties, which leads to easy damage during application, limiting its application scope in the fields of filtration, separation, etc.

Method used

Physical and chemical modification is performed by using a combination of a silane coupling agent (R'-Si-R3) of a specific chemical structure and a protonic acid catalyst to form a stable coating crosslinked on the surface of the porous membrane, thereby enhancing the mechanical properties of the membrane.

Benefits of technology

This method significantly improves the mechanical properties of the porous membrane, including the increase of tensile strength and elongation at break, while almost no affecting the resistance of the fluid through the membrane pore structure and the dissolution and precipitation performance of the porous membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118454476B_ABST
    Figure CN118454476B_ABST
Patent Text Reader

Abstract

The invention discloses a reinforced porous membrane and a preparation method thereof, comprising the following steps: (1) dispersing a silane coupling agent having a chemical formula of R'-Si-R3 in an organic solvent, and adding a protonic acid catalyst to obtain a coating liquid; (2) applying the coating liquid obtained in step (1) to the surface of the porous membrane, and then heating and drying the porous membrane to cause the silane coupling agent to undergo a cross-linking reaction and remove the organic solvent. The present invention utilizes a silane coupling agent (R'-Si-R3) of a specific chemical structure, and under the catalytic action of a protonic acid catalyst, cross-linking is performed on the surface of the porous membrane structure to form a stable coating after heating, thereby improving the mechanical strength of the porous membrane by at least about 15%, and improving the elongation at break by 30%-100%, and the coating hardly affects the resistance of the fluid through the membrane pore structure, and does not affect the dissolution and precipitation during the actual use of the porous membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microporous filter membranes, and specifically relates to a reinforced porous membrane and a preparation method thereof. Background Art

[0002] Porous film material is a material that is widely used in separation, filtration, purification, and lightweight structure. The large number of pores in the internal structure of this material will reduce its mechanical properties compared to membrane structures of the same material, homogeneity, and no pore defects, resulting in lower mechanical strength, elongation at break, etc., which limits the application scenarios of porous film materials.

[0003] For example, when a porous PES filter membrane (taking a filter membrane product with a nominal pore size of 0.22 microns as an example) is made into a disc filter, the membrane is often damaged due to ultrasonic welding, which affects the integrity of the filter. This is because the toughness of the porous PES membrane is significantly lower than that of the homogeneous pure membrane, and its elongation at break is reduced from about 52% of the homogeneous membrane to about 25% of the porous membrane, or even lower.

[0004] Improving the mechanical properties of porous membranes, such as strength and toughness, can eliminate the application limitations of porous membranes caused by the decline in mechanical properties. At the same time, the application of existing porous membranes can open up a wider process window and reduce process requirements and costs.

[0005] The technical means to enhance the mechanical properties of porous membranes include: 1. Using higher molecular weight polymer raw materials to prepare porous membranes; 2. Composite the porous membrane with a support layer that provides mechanical strength; 3. Doping fillers (such as carbon nanotubes, various nanoparticles, macromolecular compounds, etc.).

[0006] 1. Use higher molecular weight polymer raw materials to prepare porous membranes

[0007] Generally speaking, the higher the molecular weight of the polymer raw material, the better the mechanical properties of the material after molding, which is well known to the public. In the porous membrane preparation industry, especially in the porous filtration membrane industry, the polymer raw materials used, such as PES, PVDF, cellulose, etc., are generally monopolized by a few raw material suppliers. If porous membrane manufacturers need high molecular weight raw materials, they need to order them from the above suppliers, which has high production costs, long cycles, and cannot be supplied in batches. Therefore, this method is not popular.

[0008] 2. Composite the porous membrane with a support layer that provides mechanical strength

[0009] Using a higher strength support layer material, such as a non-woven material, and compounding it with a porous membrane is an effective means to improve the mechanical strength of the membrane. CN 1129456A teaches a method of hot-melt bonding a PTFE microfiltration porous membrane to a non-woven support layer. The prepared composite filter membrane can effectively resist external forces and prevent the filter layer from being damaged by external forces, thereby affecting the integrity of the filter membrane. However, after being prepared into a composite membrane, its gas flux will be significantly reduced. Generally, the gas flux of a polytetrafluoroethylene porous membrane before compounding is 50-80L / m2.s, while the gas flux after being prepared into a composite membrane is only 20-40L / m2.s. This is because the presence of the adhesive layer blocks part of the pore structure.

[0010] 3. Doped fillers

[0011] A. Rahimpour et al. improved the mechanical properties of PES membrane by doping a certain proportion of polyamide-polyimide copolymer in PES porous membrane materials [Synthesis of a novel poly(amide-imide)(PAI)and preparation and characterization of PAI blended polyethersulfone(PES)membranes, J. Membrane. Sci., 2008, V311, 1, p349]; Y. Wang et al. improved the mechanical properties of PES ultrafiltration membrane by doping a certain proportion of carbon nanotubes in PES porous membrane materials, and the reverse osmosis membrane prepared on the basis of the carbon nanotube / PES composite ultrafiltration membrane showed better performance [Preparation of polyethersulfone / carbonnanotube substrate for high-performance forward osmosis membrane, Desalination, 2013, V330, p70]. Generally, the extractable content of porous membrane materials prepared by doping methods cannot be guaranteed, which is restricted in some sensitive application fields, such as biopharmaceutical filtration and medical fields. Summary of the invention

[0012] In view of this, the object of the present invention is to provide a reinforced porous membrane and a preparation method thereof, which enhances the mechanical properties of the porous membrane by physical and chemical modification methods without affecting the resistance of the fluid through the membrane pore structure and the dissolution and precipitation of the porous membrane during actual use.

[0013] In order to achieve the above object, the present invention provides the following technical solutions:

[0014] The invention discloses a method for preparing a reinforced porous membrane, comprising the following steps:

[0015] (1) dispersing a silane coupling agent with a chemical formula of R'-Si-R3 in an organic solvent, and adding a protonic acid catalyst to obtain a coating liquid; R' in R'-Si-R3 is an alkyl chain with a carbon chain length of 1 to 18 carbon atoms or a perfluorinated C6 or C8 alkyl chain, and R is a methoxy group, an ethoxy group or a halogen atom;

[0016] (2) The coating liquid obtained in step (1) is applied to the surface of the porous membrane, and then the porous membrane is heated and dried to allow the silane coupling agent to undergo a cross-linking reaction and remove the organic solvent.

[0017] As a preferred technical solution, the silane coupling agent is dodecyltrimethoxysiloxane, tridecafluorooctyltrimethoxysiloxane, octadecyltriethoxysiloxane or tridecafluorooctyltriethoxysiloxane.

[0018] As a preferred technical solution, the protonic acid catalyst is hydrofluoric acid, hydrochloric acid, acetic acid, phosphoric acid, sulfuric acid or formic acid.

[0019] As a preferred technical solution, the organic solvent is ethanol, isopropanol, short-chain alkane or aromatic hydrocarbon.

[0020] As a preferred technical solution, in step (2), the coating process is dipping or spraying.

[0021] As a preferred technical solution, in step (2), the coating process is: the porous membrane is continuously unrolled and immersed in the coating liquid, the coating liquid is coated on the surface of the porous membrane, and then the dipped porous membrane is passed through an oven, the oven heats and dries the porous membrane, so that the silane coupling agent undergoes a cross-linking reaction and the organic solvent is removed, and finally the membrane is rolled up.

[0022] As a preferred technical solution, in the step (2), the heating temperature is 60-110°C.

[0023] As a preferred technical solution, the porous membrane is a PES filter membrane, a PVDF filter membrane, a PEI filter membrane or a PTFE filter membrane.

[0024] As a preferred technical solution, the porous membrane is a flat membrane or a hollow fiber membrane.

[0025] The invention also discloses a reinforced porous membrane, which is prepared by the reinforced porous membrane preparation method.

[0026] The present invention also discloses an application of a silane coupling agent and a protonic acid catalyst as a porous membrane surface enhancer, wherein the chemical structural formula of the silane coupling agent is R'-Si-R3; R' in R'-Si-R3 is an alkyl chain with a carbon chain length of 1 to 18 carbon atoms or a perfluorinated C6 or C8 alkyl chain, and R is a methoxy group, an ethoxy group or a halogen atom.

[0027] As a preferred technical solution, a silane coupling agent with a chemical formula of R'-Si-R3 and a protonic acid catalyst are mixed and coated on the surface of the porous membrane, and heated to crosslink the silane coupling agent on the surface of the porous membrane to form a coating.

[0028] The beneficial effects of the present invention are:

[0029] The present invention utilizes a silane coupling agent (R'-Si-R3) with a specific chemical structure, and under the catalytic action of a protonic acid catalyst, after heating, cross-links on the surface of the porous membrane structure to form a stable coating, thereby increasing the mechanical strength of the porous membrane by at least about 15%, and the elongation at break by 30%-100%, and the coating has almost no effect on the resistance of the fluid passing through the membrane pore structure, and does not affect the dissolution and precipitation of the porous membrane during actual use. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0031] Figure 1 Schematic diagram of the cross-linking reaction of the R'-Si-R3 silane coupling agent on the surface of the porous membrane in the present invention;

[0032] Figure 2 The present invention is a process flow chart for continuously producing reinforced porous membranes. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0034] Example 1

[0035] Take a roll of commercially available 0.22-micron PES filter membrane, and take 6 15 mm × 150 mm specimens in the unwinding direction (MD) and perpendicular to the unwinding direction (TD) of the membrane, for a total of 12 specimens.

[0036] Three MD and TD specimens of the original film were loaded on a tensile machine to test the tensile properties at a tensile rate of 50 mm / min. The test method was based on ASTM D882. The data are recorded in Table 1.

[0037] The other 6 specimens were reserved. 1000 ml of ethanol solution of dodecyl trimethoxysiloxane was prepared, wherein the mass fraction of siloxane was 7%, and 15 ml of hydrofluoric acid was added to the solution and mixed evenly. Then, the 6 specimens were immersed in the solution for 3 min, then taken out and placed in a 90°C oven for drying for 5 min. Then, the specimens were placed in a room temperature environment, and the tensile properties of the specimens were tested after 24 hours, with a tensile rate of 50 mm / min, and the test method was referred to ASTM D882. The data are recorded in Table 1.

[0038] Table 1. Mechanical properties test results of 0.22um PES membrane before and after modification with silane coupling agent

[0039] MD breaking force / N MD elongation at break / % TD breaking force / N TD elongation at break / % Original film spline 1 8.99 24.95 7.32 37.19 Original membrane spline 2 9.32 30.64 7.42 33.77 Original membrane spline 3 8.89 23.06 7.36 30.92 Average value of original film 9.06 26.22 7.37 33.96 Modified Spline 1 10.53 59.28 8.71 61.99 Modified Spline 2 9.95 41.76 9.29 78.19 Modified Spline 3 10.73 62.9 8.61 56.02 Average value of modified membrane 10.4 54.64 8.87 65.41

[0040] The test results show that after the PES membrane with a nominal pore size of 0.22 microns was modified with a silane coupling agent, the tensile strength in the MD direction increased by about 15%, the elongation at break increased by more than 100%, the tensile strength in the TD direction increased by about 20%, and the elongation at break increased by nearly 100%.

[0041] The modified membrane was prepared according to USP <661> The method shown uses 70℃ hot water for 24 hours, and the non-volatile residue NVR content after evaporation of the extract is 3.6 mg, which is less than USP <661> The upper limit of NVR is 10mg as stipulated; 2ml of the extract was taken and analyzed by HPLC. The components contained in the extract were consistent with those in the blank solvent control group, and no other substances were found to precipitate. This shows that the risk of dissolution and precipitation of porous PES membrane modified by silane coupling agent is low.

[0042] Figure 1 This is a schematic diagram of the cross-linking reaction of the R'-Si-R3 silane coupling agent on the surface of the porous membrane in the present invention (taking the dodecyltrimethoxysiloxane in Example 1 as an example). It can be seen that the present invention utilizes a silane coupling agent (R'-Si-R3) with a specific chemical structure, and under the catalytic action of a protonic acid catalyst, it is cross-linked on the surface of the porous membrane structure after heating to form a stable coating.

[0043] Example 2

[0044] Take a roll of commercially available 0.45-micron PES filter membrane, and take 6 15 mm × 150 mm specimens in the unwinding direction (MD) and perpendicular to the unwinding direction (TD) of the membrane, for a total of 12 specimens.

[0045] Three MD and TD specimens of the original film were loaded on a tensile machine to test the tensile properties. The tensile rate was 50 mm / min. The test method was based on ASTM D882. The data are recorded in Table 2.

[0046] The other 6 specimens are reserved. Prepare 1000 ml of ethanol solution of tridecafluorooctyl trimethoxysiloxane, in which the mass fraction of siloxane is 7%, and add 15 ml of dilute hydrochloric acid to the above solution and mix well. Then immerse the 6 specimens in the above solution for 3 minutes, then take them out and place them in a 90°C oven for drying for 5 minutes. Then leave the specimens at room temperature and test the tensile properties of the specimens after 24 hours. The tensile rate is 50 mm / min. The test method refers to ASTM D882. Record the data in Table 2.

[0047] Table 2. Mechanical properties test results of 0.45um PES membrane before and after modification with silane coupling agent

[0048] MD breaking force / N MD elongation at break / % TD breaking force / N TD elongation at break / % Original film spline 1 4.55 9.44 5.97 9.74 Original membrane spline 2 4.30 7.94 6.07 10.19 Original membrane spline 3 4.79 9.89 5.99 8.39 Average value of original film 4.55 9.09 6.01 9.44 Modified Spline 1 6.94 34.04 7.81 30.29 Modified Spline 2 7.38 50.24 7.93 18.29 Modified Spline 3 7.12 45.59 7.68 32.39 Average value of modified membrane 7.15 43.29 7.81 26.99

[0049] The test results show that after the PES membrane with a nominal pore size of 0.45 microns was modified with a silane coupling agent, the tensile strength in the MD direction increased by about 57%, the elongation at break increased by more than 400%, the tensile strength in the TD direction increased by about 30%, and the elongation at break increased by more than 280%.

[0050] Example 3

[0051] Take a roll of commercially available 0.65-micron PES filter membrane, and take 6 15 mm × 150 mm specimens in the unwinding direction (MD) and perpendicular to the unwinding direction (TD) of the membrane, for a total of 12 specimens.

[0052] Three MD and TD specimens of the original film were loaded on a tensile machine to test the tensile properties. The tensile rate was 50 mm / min. The test method was based on ASTM D882. The data are recorded in Table 3.

[0053] The other 6 specimens were reserved. Prepare 1000 ml of ethanol solution of octadecyl triethoxysiloxane, in which the mass fraction of siloxane was 5%, and add 10 ml of acetic acid to the solution and mix well. Then immerse the 6 specimens in the solution for 5 minutes, then take them out and place them in a 110°C oven for drying for 3 minutes. Then leave the specimens at room temperature and test the tensile properties of the specimens after 24 hours. The tensile rate was 50 mm / min. The test method was based on ASTM D882. The data are recorded in Table 3.

[0054] Table 3. Mechanical properties test results of 0.65um PES membrane before and after modification with silane coupling agent

[0055] MD breaking force / N MD elongation at break / % TD breaking force / N TD elongation at break / % Original film spline 1 2.50 5.99 4.21 14.24 Original membrane spline 2 3.02 13.19 3.65 5.99 Original membrane spline 3 2.60 4.04 3.47 4.34 Average value of original film 2.71 7.74 3.78 8.19 Modified Spline 1 4.02 5.81 4.69 11.06 Modified Spline 2 4.08 16.15 4.40 15.14 Modified Spline 3 4.67 34.94 4.02 18.89 Average value of modified membrane 4.38 19.17 4.33 15.03

[0056] The test results show that after the PES membrane with a nominal pore size of 0.65 microns was modified with a silane coupling agent, the tensile strength in the MD direction increased by about 60%, the elongation at break increased by more than 250%, the tensile strength in the TD direction increased by about 15%, and the elongation at break increased by more than 80%.

[0057] Examples 1-3 show that PES filter membranes with different pore sizes, after being treated with a silane coupling agent (R'-Si-R3) with a specific chemical structure and a protonic acid catalyst according to the present invention, all exhibit significantly improved mechanical properties.

[0058] Example 4

[0059] Take a roll of commercially available 0.22-micron PVDF filter membrane, and take 6 15 mm × 150 mm specimens in the unwinding direction (MD) and perpendicular to the unwinding direction (TD) of the membrane, for a total of 12 specimens.

[0060] Three MD and TD specimens of the original film were loaded on a tensile machine to test the tensile properties at a tensile rate of 50 mm / min. The test method was based on ASTM D882. The data are recorded in Table 4.

[0061] The other 6 specimens were reserved. 1000 ml of ethanol solution of dodecyl trimethoxysiloxane was prepared, wherein the mass fraction of siloxane was 7%, and 15 ml of phosphoric acid was added to the solution and mixed evenly. The 6 specimens were then immersed in the solution for 3 min, then taken out and placed in a 90°C oven for drying for 5 min. The specimens were then placed in a room temperature environment, and the tensile properties of the specimens were tested after 24 hours, with a tensile rate of 50 mm / min, and the test method was based on ASTM D882. The data are recorded in Table 4.

[0062] Table 4. Mechanical properties test results of 0.22um PVDF membrane before and after modification with silane coupling agent

[0063] MD breaking force / N MD elongation at break / % TD breaking force / N TD elongation at break / % Original film spline 1 4.50 6.59 4.93 10.58 Original membrane spline 2 4.82 7.04 4.49 9.69 Original membrane spline 3 5.05 7.34 4.03 6.59 Average value of original film 4.79 6.99 4.48 8.95 Modified Spline 1 5.50 12.74 6.11 27.01 Modified Spline 2 4.76 14.09 5.47 17.19 Modified Spline 3 5.82 29.24 5.51 23.59 Average value of modified membrane 5.36 19.69 5.70 22.59

[0064] The test results show that after the PVDF membrane with a nominal pore size of 0.22 microns is modified with a silane coupling agent, the tensile strength in the MD direction increases by about 12%, the elongation at break increases by more than 280%, the tensile strength in the TD direction increases by about 27%, and the elongation at break increases by more than 250%.

[0065] Comparison between Example 1 and Example 4 shows that the present invention has a significant effect on improving the mechanical properties of microporous membranes of different materials after treatment with a silane coupling agent (R'-Si-R3) with a specific chemical structure and a protonic acid catalyst.

[0066] Example 5

[0067] A commercially available 0.22 micron PES sterilizing filter membrane was cut into 20 discs with a diameter of 50 mm, 10 of which were not modified and directly loaded into a disc filter with barbed interfaces upstream and downstream, and prepared into a D50 disc filter by a high-frequency ultrasonic welding process; another group of 10 discs were modified by a method similar to that described in Example 1, and then similarly loaded into a disc filter and prepared into a D50 disc filter by a high-frequency ultrasonic welding process. Subsequently, the two groups of filters were subjected to a bacterial challenge experiment, and the challenge method referred to ASTM-F838 to evaluate the filter's interception efficiency and integrity for bacteria, and the results are summarized in Table 5.

[0068] Table 5. Bacterial challenge test results of D50 disc filters loaded with different membranes

[0069] serial number Filter loaded with unmodified membrane Filters loaded with modified membranes 1 Downstream sterility Downstream sterility 2 Bacteria leak downstream and cannot be counted Downstream sterility 3 Downstream sterility Downstream sterility 4 Downstream sterility Downstream sterility 5 Downstream sterility Downstream sterility 6 Bacteria leak downstream and cannot be counted Downstream sterility 7 Bacteria leak downstream and cannot be counted Downstream sterility 8 Downstream sterility Downstream sterility 9 Downstream sterility Downstream sterility 10 Bacteria leak downstream and cannot be counted Downstream sterility Pass Rate 60% 100%

[0070] It can be seen from the data in Table 5 that the filter equipped with the modified membrane has a bacterial challenge pass rate of 100%, while the filter equipped with the unmodified membrane has a bacterial challenge pass rate of only 60%. After unpacking the filter that failed the bacterial challenge, it was found that the part where the membrane contacted the filter weld had visible mechanical damage, resulting in bacterial leakage. The mechanical damage to the membrane was caused by the ultrasonic welding process. Therefore, compared with the unmodified membrane, the modified membrane has looser requirements on the packaging process of the filter and a higher product yield.

[0071] Example 6

[0072] Figure 2 The process flow chart of continuously producing enhanced porous membrane is as shown in the figure. A roll of PEI filter membrane is placed at the unwinding position. An isopropanol solution of tridecafluorooctyl triethoxysiloxane is prepared, in which the mass fraction of siloxane in the solution is 10%, and formic acid is dropped into the solution. After mixing evenly, the solution is poured into a silane coupling agent tank. The PEI filter membrane is continuously unrolled and immersed in the silane coupling agent tank. The dipped PEI filter membrane is then passed through an oven. The oven heats and dries the PEI filter membrane, so that the silane coupling agent undergoes a cross-linking reaction and the organic solvent is removed. Finally, the membrane is rolled up.

[0073] According to the tensile performance test, the tensile strength of the PEI filter membrane produced by the above process is increased by about 17% compared with the original membrane, and the elongation at break is increased by 38%.

[0074] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a reinforced porous membrane, characterized in that: The following steps are involved: (1) dispersing tridecafluorooctyl trimethoxysiloxane in an organic solvent, wherein the mass fraction of tridecafluorooctyl trimethoxysiloxane is 7%, and adding a protonic acid catalyst to obtain a coating liquid; (2) The porous membrane is continuously unrolled and immersed in the coating liquid, so that the coating liquid is coated on the surface of the porous membrane. The porous membrane after dipping is then passed through an oven. The oven heats and dries the porous membrane to cause a cross-linking reaction of the silane coupling agent and remove the organic solvent, and finally the membrane is rolled up.

2. The method for preparing a reinforced porous membrane according to claim 1, characterized in that: The protonic acid catalyst is hydrofluoric acid, hydrochloric acid, acetic acid, phosphoric acid, sulfuric acid or formic acid.

3. The method for preparing the reinforced porous membrane according to claim 1, characterized in that: The organic solvent is ethanol, isopropanol, short-chain alkane or aromatic hydrocarbon.

4. The method for preparing a reinforced porous membrane according to claim 1, characterized in that: In the step (2), the heating temperature is 60-110°C.

5. The method for preparing a reinforced porous membrane according to any one of claims 1 to 4, characterized in that: The porous membrane is a PES filter membrane, a PVDF filter membrane, a PEI filter membrane or a PTFE filter membrane.

6. The method for preparing a reinforced porous membrane according to any one of claims 1 to 4, characterized in that: The porous membrane is a flat membrane or a hollow fiber membrane.

7. A reinforced porous membrane, characterized in that: The reinforced porous membrane is prepared by the method for preparing the reinforced porous membrane according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Composite porous polytetrafluoroethylene membrane

    CN1129456A